Ips Engraver Beetles, Ips spp. (Insecta: Coleoptera: Curculionidae: Scolytinae) - Jeffrey M. Eickwort; Albert E. Mayfield III; John L. Foltz (EDIS, 2007)
EENY-388, a 7-page illustrated fact sheet by Jeffrey M. Eickwort, Albert E. Mayfield III, and John L. Foltz, describes three species of pine bark beetles in the genus Ips -- the sixspined ips, I. calligraphus (Germar); the eastern fivespined ips, I. grandicollis (Eichloff); and the small southern pine engraver, I. avulsus (Eichloff) -- which live predominantly in the inner bark of stressed pines in the southern United States, where they breed and feed on phloem tissue. Includes selected references. Published by the UF Department of Entomology and Nematology, September 2006.